RELATIONSHIP BETWEEN EDUCATION AND CULTURE BY BERNARD SCHLINK’S BOOK ‘THE READER’ - Nurhan ULUÇ (Fırat University, 2021)
It is an indisputable fact that education has guided the roles of individuals in society from past to present. In this context, it is also important for individuals to communicate with other individuals in the society. The education offered in any country also has an aspect that reflects the culture of that country. Therefore, the relationship between education and culture is one of the important factors that direct an individual's adaptation to society. Education and culture, without a doubt, form a whole with societies and individuals living within societies. It can even be said that this integrity has continued for generations in the direction of different methods and ideas. However, it is necessary to address the phenomenon of war in this interaction that has been going on for generations. War has made its brutal mark on the educational process and the cultural adventure of individuals and societies in every period. In this context, Bernhard Schlink's ‘The Reader’, one of the most important authors of German literature after World War II, reveals clearly how the conditions of this period lead human life. In Bernhard Schlink's "The Reader", it can be said that this situation affects not only the lives and socio-economic conditions of the characters, but also the communication, human relations of individuals living in society and the perspective of the society towards the individual. In this study, it is aimed to examine the reflection of educational and cultural phenomena on society and its effects on the lives and preferences of the individuals who make up the society within the framework of examples in Bernhard Schlink’s book ‘The Reader’.